A multi-process model for the photocatalytic reduction of CO2. Issue 36 (13th September 2022) - Sun, Chen; Xuan, Yimin; Zhang, Kai
Abstract : An innovative multi-process photocatalytic module integrating light absorption, excitation, carrier transport and surface reactions. Abstract : The photocatalytic conversion of CO2 to fuel and valuable carbon compounds is a feasible method for the large-scale reuse of CO2 . However, it involves complex multi-processes and physical phenomena, limiting the enhanced performance of photocatalysis. Consequently, building a comprehensive model is necessary. Herein, we present a multi-process computational framework for simulating the whole photocatalytic CO2 reduction process. In this work, the physical and chemical properties of the catalysts were determined by density functional theory (DFT). Specifically, we employed a framework consisting of an optical absorption and carrier transport model to simulate the conversion process from photons to carriers, a micro-kinetic model to describe the surface catalytic reaction process, and a continuum transport model to calculate the mass transfer process between the solution and surface. Using this multiscale model, we simulated and analyzed the photocatalytic processes of rGO-MoS2 /PPy (MoS2 and polymer polypyrrole on reduced graphene oxide). The simulation clarified the key factors affecting the catalyst activity and selectivity. Moreover, the energy loss in different processes was also clarified, which showed that the model can be a theoretical analysis tool for analyzing and improving the photocatalytic performance of materials.